Transcriptomic and Phenotypic Analysis of a spoIIE Mutant in Clostridium beijerinckii - Diallo, Mamou; Kint, Nicolas; Monot, Marc; Collas, Florent; Martin-Verstraete, Isabelle; van der Oost, John; Kengen, Servé W. M.; López-Contreras, Ana M. (Frontiers in Microbiology, 2020)
SpoIIE is a phosphatase involved in the activation of the first sigma factor of the forespore, σF, during sporulation. A ΔspoIIE mutant of Clostridium beijerinckii NCIMB 8052, previously generated by CRISPR-Cas9, did not sporulate but still produced granulose and solvents. Microscopy analysis also showed that the cells of the ΔspoIIE mutant are elongated with the presence of multiple septa. This observation suggests that in C. beijerinckii, SpoIIE is necessary for the completion of the sporulation process, as seen in Bacillus and Clostridium acetobutylicum. Moreover, when grown in reactors, the spoIIE mutant produced higher levels of solvents than the wild type strain. The impact of the spoIIE inactivation on gene transcription was assessed by comparative transcriptome analysis at three time points (4 h, 11 h and 23 h). Approximately 5% of the genes were differentially expressed in the mutant compared to the wild type strain at all time points. Out of those only 12% were known sporulation genes. As expected, the genes belonging to the regulon of the sporulation specific transcription factors (σF, σE, σG, σK) were strongly down-regulated in the mutant. Inactivation of spoIIE also caused differential expression of genes involved in various cell processes at each time point. Moreover, at 23 h, genes involved in butanol formation and tolerance, as well as in cell motility, were up-regulated in the mutant. In contrast, several genes involved in cell wall composition, oxidative stress and amino acid transport were down-regulated. These results indicate an intricate interdependence of sporulation and stationary phase cellular events in C. beijerinckii.